Leadership Perspectives on Local Health Department Workforce Development: A Regional Training Needs Assessment. Issue 2 (March 2022) - Kulik, Phoebe K. G.; Leider, Jonathon P.; Beck, Angela J.
Abstract : The public health workforce broadly—across disciplines, tiers, and settings—requires strategic skills to advance population health outcomes. In early 2020, the Region V Public Health Training Center conducted a competency-based training needs assessment survey with all 501 local health departments in the 6-state region, including small agencies that were previously excluded from available national data sources. Health officials or designees from 290 agencies responded (58% response rate) with perspectives regarding the ability of their staff to sufficiently apply strategic skills. Findings highlight training needs among the region's local governmental public health workforce and differences in those needs by the size of population served by the agency. Notable training priorities include the skill domains of Budgeting & Financial Management and Change Management, among others. Abstract : Supplemental Digital Content is Available in the Text.